2020
DOI: 10.3892/ijo.2020.5006
|View full text |Cite
|
Sign up to set email alerts
|

SORBS1 serves a metastatic role via suppression of AHNAK in colorectal cancer cell lines

Abstract: Cbl-associated protein (CAP) is encoded by the sorbin and SH3 domain-containing 1 (SORBS1) gene. CAP has been reported to be associated with the actin cytoskeleton, receptor tyrosine kinase signaling and cell adhesion through interactions with various proteins. It may be hypothesized that SORBS1 has numerous unknown functions, which may include providing a favorable condition for metastasis. Although CAP has been demonstrated to possess a number of functions, the role of this protein has only been reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Moreover, it promoted epithelial-to-mesenchymal transition (EMT) of colorectal cancer (CRC) cells [ 55 ] and had the same characteristics in ovarian cancer [ 51 ] and prostate cancer [ 50 ]. SORBS1 overexpression promoted CRC growth and migration via inhibition of AHNAK expression [ 56 ], while SORBS1 was downregulated in breast cancer and led to poor prognosis [ 47 ]. Silencing of SORBS1 promoted the EMT process and attenuated chemical drug sensitivity, and it is a potential inhibitor of metastasis in cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it promoted epithelial-to-mesenchymal transition (EMT) of colorectal cancer (CRC) cells [ 55 ] and had the same characteristics in ovarian cancer [ 51 ] and prostate cancer [ 50 ]. SORBS1 overexpression promoted CRC growth and migration via inhibition of AHNAK expression [ 56 ], while SORBS1 was downregulated in breast cancer and led to poor prognosis [ 47 ]. Silencing of SORBS1 promoted the EMT process and attenuated chemical drug sensitivity, and it is a potential inhibitor of metastasis in cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…SORBS1 and FFAR4 were two of DEGs from the yellow module in the DS group. SORBS1 was associated with insulin signaling pathway [40], glucose homeostasis [41,42], cancer growth and migration [43,44], etc. FFAR4 have similar functions including glucose and fatty acid metabolism [45,46], glucose-dependent insulinotropic polypeptide secretion [47], cell cancelation [48,49], etc.…”
Section: Discussionmentioning
confidence: 99%
“…SORBS1 encodes a CasitasB.1ineagelymphoma (CBL)-associated protein that functions in the signaling and stimulation of insulin, and it also been confirmed to be related to COPD [80][81][82] . Studies have found that SORBS1 can participate in immune-related gene signal transduction, and its increased expression is closely related to poor prognosis in cervical cancer 83 , gastric cancer 84 , prostate cancer 85 , and colorectal cancer 86 . However, the exact role and diagnostic significance of SORBS1 in BRCA are not yet clear.…”
Section: Prognostic Gene-drug Interaction Network Analysismentioning
confidence: 99%